The master and his emissary : the divided brain and the making of the Western world - McGilchrist, Iain (Yale University Press, 2019)
A new edition of the bestselling classic - published with a special introduction to mark its 10th anniversary This pioneering account sets out to understand the structure of the human brain - the place where mind meets matter. Until recently, the left hemisphere of our brain has been seen as the 'rational' side, the superior partner to the right. But is this distinction true? Drawing on a vast body of experimental research, Iain McGilchrist argues while our left brain makes for a wonderful servant, it is a very poor master. As he shows, it is the right side which is the more reliable and insightful. Without it, our world would be mechanistic - stripped of depth, colour and value.